2010
DOI: 10.1007/s10646-010-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

Transfer modelling and toxicity evaluation of the effluent from an installation of cleansing and uranium recovery using a battery of bioassays

Abstract: On July 7, 2008, a leak of effluent from an Installation of Cleansing and Uranium Recovery (Tricastin, France) led to the spillage of uranium in a stream. The acute toxicity of the effluent was evaluated, and compared to the toxicity of uranium nitrate in bioassays using several organisms: Chlamydomonas reinhardtii, Daphnia magna, Chironomus riparius and Danio rerio. A sediment bioassay was also performed on C. riparius using water and sediment sampled along the river. Results showed that effluent EC(50) 72 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…It is a main by-product of the nuclear fuel cycle, it is used as counterweights in the aircraft industry, in biological shielding for radiation protection and is used as armour penetrator in military conventional ammunitions. High levels of natural [8] and depleted uranium [9] have already been observed, either in the vicinity of former mining sites or after accidental spillage of industrial sites. With the growing world nuclear energy demand, DU concentration in the geosphere is expected to increase in the next decades [10], raising concerns on the long-term effects of this chemical on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is a main by-product of the nuclear fuel cycle, it is used as counterweights in the aircraft industry, in biological shielding for radiation protection and is used as armour penetrator in military conventional ammunitions. High levels of natural [8] and depleted uranium [9] have already been observed, either in the vicinity of former mining sites or after accidental spillage of industrial sites. With the growing world nuclear energy demand, DU concentration in the geosphere is expected to increase in the next decades [10], raising concerns on the long-term effects of this chemical on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Especially near the U mill tailings, U dust particles can be easily washed out by precipitation into surface water. The U concentration in surface water may range from 0.02 μg/L to 3 mg/L, depending on the geological conditions [24]. Uranium may accumulate in bone, liver and kidney of an organism, but may not be biomagnified [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated chronic toxicity of waterborne depleted uranium on the life cycle and physiology of Daphnia magna . , Uranium is naturally found in freshwaters at concentrations ranging from ≤6 μg L −1 to 2 mg L −1 in the vicinity of uraniferous sites. Locally, these levels are largely exceeded due to anthropogenic activities associated with the use of uranium in nuclear fuel or weapons. Uranium is a heavy metal and its chemical toxicity is commonly considered of much greater concern in comparison to its radiotoxicity. , Uranium toxic effects were showed to increase across three successively exposed generations, highlighting the necessity for multigenerational toxicity tests in support of ecological risk assessment . Measuring feeding rates with a radiomarker technique showed that a reduction in carbon assimilation was probably involved in the response to uranium.…”
Section: Introductionmentioning
confidence: 99%